Validation of SpO₂ and Heart Rate Monitoring in a Smart Patient Bed System for Home Care - Eko Arianto; Dion Sulistyo; Syarif Hidayat; Sebastianus Christian Dwiatmojo (Journal of Renewable Energy and Smart Device, 2026)
Continuous monitoring of vital signs is essential in-patient care, especially for home care and hospital-at-home applications requiring long-term, non-diagnostic observation. Oxygen saturation (SpO₂) and heart rate are commonly monitored; however, conventional systems rely on standalone or wearable devices that may reduce patient comfort and compliance. Integrating monitoring into a smart patient bed system enables passive and continuous data acquisition without interfering with patient activity. This study aims to validate the performance of SpO₂ and heart rate monitoring integrated into a smart patient bed system for home care applications. The main contribution is the experimental validation of a smart patient bed system as a non-diagnostic monitoring solution, offering an alternative to wearable systems. Validation was performed by comparing measurements from the proposed system with a commercial pulse oximeter and a bedside patient monitor under resting conditions. Absolute error, mean absolute error, and standard deviation were calculated to evaluate accuracy and stability. Results show good agreement with both reference devices. The mean absolute error was below 1% for SpO₂ and below 1 bpm for heart rate, with low standard deviations indicating stable performance. In conclusion, the system provides a reliable solution for continuous vital sign monitoring in home care environments. This study also demonstrates the feasibility of integrating optical sensing into a smart patient bed system for long-term monitoring